2014
DOI: 10.1016/j.cub.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

The Spartan Ortholog Maternal Haploid Is Required for Paternal Chromosome Integrity in the Drosophila Zygote

Abstract: The animal sperm nucleus is characterized by an extremely compacted organization of its DNA after the global replacement of histones with sperm-specific nuclear basic proteins, such as protamines. In the absence of DNA repair activity in the mature gamete, the integrity of the paternal genome is potentially challenged by the unique topological constraints exerted on sperm DNA. In addition, the maintenance of paternal DNA integrity during the rapid remodeling of sperm chromatin at fertilization has long been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 41 publications
4
60
2
Order By: Relevance
“…Moreover, premature cataract has been observed in RJALS and in a hypomorphic SPRTN mouse model, which is a general sign of failure to maintain postmitotic tissue homeostasis (Maskey et al., 2014, Ruijs et al., 2003). A replication-independent function of SPRTN also is indicated by results in flies, where SPRTN is recruited to chromatin independently of replication (Delabaere et al., 2014). Consistently, we found that arrested L1 worm larvae, in which no replication is occurring, are extremely sensitive to acute formaldehyde exposure if they lack SPRTN.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, premature cataract has been observed in RJALS and in a hypomorphic SPRTN mouse model, which is a general sign of failure to maintain postmitotic tissue homeostasis (Maskey et al., 2014, Ruijs et al., 2003). A replication-independent function of SPRTN also is indicated by results in flies, where SPRTN is recruited to chromatin independently of replication (Delabaere et al., 2014). Consistently, we found that arrested L1 worm larvae, in which no replication is occurring, are extremely sensitive to acute formaldehyde exposure if they lack SPRTN.…”
Section: Discussionmentioning
confidence: 82%
“…Initial studies suggested that SPRTN is important for regulating translesion synthesis (TLS), although with conflicting reports on the actual molecular mechanism (Centore et al., 2012, Davis et al., 2012, Ghosal et al., 2012, Juhasz et al., 2012, Machida et al., 2012, Mosbech et al., 2012). Importantly, however, the severe phenotypes observed in flies, mice, and human cells have been shown to be unrelated to TLS, suggesting that SPRTN maintains genome integrity by an unknown mechanism distinct from TLS (Delabaere et al., 2014, Lessel et al., 2014, Maskey et al., 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this interpretation, our previous study identified interactions between the Spartan SprT domain and DNA polymerase δ (8). On the other hand, a DNA replication-independent function of Spartan has also been suggested in C. elegans and D. melanogaster (20,53). Thus, it remains unclear whether the Spartan-dependent DPC repair pathway is always coupled with DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have revealed additional, crucial functions of SPRTN in maintaining genome stability, supposedly independently of TLS. Loss of function of Drosophila melanogaster Sprtn causes the elimination of paternal genomes after fertilization owing to excessive genome instability 54 . The authors postulated that packaging of paternal DNA within the sperm induces specific types of DNA damage, which need to be repaired to allow proper replication and faithful chromosome segregation.…”
Section: Interplay Of Dpc-repair Pathwaysmentioning
confidence: 99%